Evaluating the Effectiveness of External Molecular Proficiency Testing in the Global Polio Laboratory Network, 2021–2022 - Gerloff, Nancy; Burns, Cara C. (Pathogens (Basel), 2024)
In the Global Poliovirus Laboratory Network (GPLN), participation and successful completion in annual proficiency test (PT) panels has been a part of the WHO accreditation process for decades. The PT panel is a molecular external quality assessment (mEQA) that evaluates laboratory preparedness, technical proficiency, the accuracy of data interpretation, and result reporting. Using the Intratypic Differentiation (ITD) real-time RT-PCR kits from CDC, laboratories run screening assays and report results in accordance with the ITD algorithm to identify and type polioviruses. The mEQA panels consisted of 10 blinded, non-infectious lyophilized RNA transcripts, including programmatically relevant viruses and targets contained in the real-time PCR assays. Sample identities included wildtype, vaccine-derived (VDPV), Sabin-like polioviruses, enterovirus, and negatives, as well as categories of invalid and indeterminate. The performance of individual laboratories was assessed based on the laboratory’s ability to correctly detect and characterize the serotype/genotype identities of each sample. The scoring scheme assessed the laboratory readiness following GPLN guidelines. Laboratories receiving mEQA scores of 90 or higher passed the assessment, scores of less than 90 failed and required remedial actions and re-evaluation. In 2021 and 2022, 123 and 129 GPLN laboratories were invited to request the annual PT panel, and 118 and 127 laboratories submitted results, respectively. The overall results were good, with 86% and 91.5% of laboratories passing the PT panel on their first attempt in 2021 and 2022, respectively. Most labs scored the highest score of 100, and less than one quarter scored between 90 and 95. Less than 10% of submitting laboratories failed the PT, resulting in in-depth troubleshooting to identify root causes and remediations. Most of these laboratories were issued a second PT panel for repeat testing, and almost all laboratories passed the repeat PT panel. The results of the 2021 and 2022 annual mEQA PTs showed that, despite the COVID-19 pandemic, the performance remained high in the GPLN, with most labs achieving the highest score. For these labs, the real-time PCR assay updates that were implemented during 2021–2022 were carried out with full adherence to procedures and algorithms. Even initially failing labs achieved passing scores after remediation.